Impaired oxidative stress response characterizes HUWE1-promoted X-linked intellectual disability. Issue 1 (December 2017) - Bosshard, Matthias; Aprigliano, Rossana; Gattiker, Cristina; Palibrk, Vuk; Markkanen, Enni; Backe, Paul; Pellegrino, Stefania; Raymond, F.; Froyen, Guy; Altmeyer, Matthias; Bjørås, Magnar; Dianov, Grigory; et al.
Abstract Mutations in the HECT, UBA and WWE domain-containing 1 (HUWE1 ) E3 ubiquitin ligase cause neurodevelopmental disorder X-linked intellectual disability (XLID). HUWE1 regulates essential processes such as genome integrity maintenance. Alterations in the genome integrity and accumulation of mutations have been tightly associated with the onset of neurodevelopmental disorders. ThoughHUWE1 mutations are clearly implicated in XLID and HUWE1 regulatory functions well explored, currently much is unknown about the molecular basis of HUWE1-promoted XLID. Here we showed that the HUWE1 expression is altered and mutation frequency increased in three different XLID individual (HUWE1 p.R2981H, p.R4187C andHUWE1 duplication) cell lines. The effect was most prominent in HUWE1 p.R4187C XLID cells and was accompanied with decreased DNA repair capacity and hypersensitivity to oxidative stress. Analysis of HUWE1 substrates revealed XLID-specific down-regulation of oxidative stress response DNA polymerase (Pol) λ caused by hyperactive HUWE1 p.R4187C. The subsequent restoration of Polλ levels counteracted the oxidative hypersensitivity. The observed alterations in the genome integrity maintenance may be particularly relevant in the cortical progenitor zones of human brain, as suggested by HUWE1 immunofluorescence analysis of cerebral organoids. These results provide evidence that impairments of the fundamental cellular processes, like genome integrity maintenance, characterize HUWE1-promoted XLID.